Perinatal outcomes of fetal intra-abdominal umbilical vein varix: a multicenter cohort study. (18th October 2021) - Novoa, Victoria; Shazly, Sherif; Ibirogba, Eniola R.; Sutton, Laura; Tonni, Gabriele; Prefumo, Federico; Sepulveda, Waldo; Araujo Júnior, Edward; Werner, Heron; Trinidad, Mari Charisse; Ruano, Rodrigo
Abstract: Objectives: To investigate the perinatal outcomes of fetuses with antenatal diagnoses of intra-abdominal umbilical vein varix (UVV). Methods: A multicenter retrospective study was conducted in four countries on fetuses diagnosed with intra-abdominal UVV between 2012 and 2019. Collected data included gestational age (GA), UVV maximum diameter at diagnosis and delivery, associated anatomical and chromosomal anomalies, birth weight, and neonatal outcomes. Results: Twenty fetuses were identified, of which 20% had associated chromosomal and/or anatomical abnormalities, most resulting in poor outcomes (either intrauterine fetal death or pregnancy termination). Mean maternal age was 34.1 ± 7.0 years, UVV was diagnosed at 26.5 ± 4.5 weeks of GA on average with a maximum diameter of 12.0 ± 4.0 mm. Mean GA at delivery was 35.4 ± 5.6 weeks. Survival rate was 85%. Conclusion: Our study shows a satisfactory outcome when intra-abdominal UVV is an isolated finding, with minimal obstetrical and perinatal consequences. The prognosis is worse when UVV is associated with other anomalies.